Nutrients in litter of four eucalyptus clones under an Integrated Crop-Livestock-Forest System (CLFS) - Velozo, Amanda Prudente; Pacheco, Abílio Rodrigues; Calil, Francine Neves; Silva-Neto, Carlos de Melo (Revista Ecologia e Nutrição Florestal - ENFLO, 2022)
The objective of this study was to evaluate the biomass production and nutrient stock in the accumulated litter of a plantation with four eucalyptus clones (AEC-2034 ((Eucalyptus camaldulensis x E. grandis) x E. urophylla)), AEC-2111 (E. urophylla x (E. camaldulensis x E. grandis)), AEC-007 (E. toreliana x E. citriodora) and AEC-0043 (E. citriodora x E. toreliana)) at four and a half years under an integrated crop-livestock-forest system (CLFS) in Inaciolândia, Goiás, Brazil. A template of an area of ​​0.0625 m² was used for the litter collection (leaves, branches, bark and miscellaneous). Thus, 20 litter samples were collected at random from each clone, totaling 80 samples. All of the material was processed in the laboratory through drying, weighing and grinding to determine biomass and analyze the nutritional content. The results obtained were an accumulation in the average total above ground biomass production estimated at 6.07 Mg ha-1 for the AEC-2034 clone, 5.20 Mg ha-1 for the AEC-2111 clone, 3.41 Mg ha-1 1 for the AEC-007 clone and 3.23 Mg ha-1 for the AEC-0043 clone. The leaf component showed the highest total accumulation in all clones. Nitrogen (N) was the element which presented the highest accumulation in the litter for all clones. The greatest accumulation of litter biomass occurred for the AEC-2034 clone, and the most representative component was leaves. The AEC-2034 clone showed the highest nutrient stock in the litter and the AEC-0043 clone presented the lowest stock. Nitrogen (N) was the macronutrient with the highest accumulation in the evaluated components, and iron (Fe) was the micronutrient. Based on litter and nutrient return, the most suitable clone in the CLFS system in this region is the AEC-2034 clone.